2020
DOI: 10.1186/s12876-020-01336-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-course Rifaximin therapy efficacy and lactulose hydrogen breath test in Chinese patients with diarrhea-predominant irritable bowel syndrome

Abstract: Background: Gut microbiota alterations including small intestinal bacterial overgrowth (SIBO) might play a role in pathogenesis of irritable bowel syndrome (IBS). Rifaximin could effectively and safely improve IBS symptoms. The aim of this study was to investigate the effect of rifaximin on Gastrointestinal (GI) symptoms, quality of life (QOL) and SIBO eradication in Chinese IBS-D patients. Methods: This study included 78 IBS-D patients defined by the Rome IV criteria. Patients received 400 mg rifaximin twice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The LHBT was completed for all IBS-D patients according to a standard procedure. And according to our previous research [ 13 ], when the baseline value of H2 ≥ 20 p.p.m and/or a rise of > 20 p.p.m. from baseline in H2 within 90 min of lactulose administration, the LHBT should be considered a presence of SIBO.…”
Section: Methodsmentioning
confidence: 81%
“…The LHBT was completed for all IBS-D patients according to a standard procedure. And according to our previous research [ 13 ], when the baseline value of H2 ≥ 20 p.p.m and/or a rise of > 20 p.p.m. from baseline in H2 within 90 min of lactulose administration, the LHBT should be considered a presence of SIBO.…”
Section: Methodsmentioning
confidence: 81%
“…Although there is no generally accepted consensus on SIBO therapy, rifaximin is frequently used [ 29 ]. We observed that two weeks administration of 400 mg rifaximin three times daily resulted in a significant decrease in LHBT values, but the average concentration of expired hydrogen was still above the SIBO cut-off level (20 ppm) ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, according to a novel Indian study, IBS patients with SIBO on upper gut aspirate culture selected for antibiotics treatment showed a response rate as high as 87% 130 . These improved antibiotics responses were able to be reproduced in subsequent studies from China and the United States using the lactulose H 2 breath test, although studies with a larger sample size are needed on this issue 131,132 …”
Section: Microbiota‐directed Therapeutic Interventions For Fgidsmentioning
confidence: 99%
“… 130 These improved antibiotics responses were able to be reproduced in subsequent studies from China and the United States using the lactulose H 2 breath test, although studies with a larger sample size are needed on this issue. 131 , 132 …”
Section: Microbiota‐directed Therapeutic Interventions For Fgidsmentioning
confidence: 99%